Perubahan Iklim sebagai Ancaman Keamanan Internasional: Studi Kasus Konflik Iklim di Darfur, Sudan - Zadrach Barenz Windessy; Imam Nugraha (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This paper explores how climate change has contributed to the armed conflict in Darfur, Sudan, by emphasizing the human security perspective. Prolonged drought, desertification, and resource scarcity have intensified tensions between farming and pastoralist communities. Using a case study method and the Human Security framework, this study finds that ecological stress acts as a threat multiplier in conflict-prone areas. Data from IPCC, SIPRI, and UNHCR reports highlight how environmental degradation worsens structural vulnerabilities and fuels horizontal violence. The analysis shows that climate change is not only an environmental issue but also a serious security concern in fragile states. The failure of state institutions to equitably manage natural resources exacerbates the crisis. Therefore, a long-term, multi-sectoral policy response is urgently needed. Integrating climate resilience into international security strategies is essential to protect basic human rights.